Efektivitas Penerapan Model Pembelajaran Value Clarification Technique Terhadap Hasil Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam Di Kelas VIII MTsN Padang Panjang - Rima Maulidia Putri; Juliwis Kardi; Diana Sartika (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The background of this study is the large number of students who scored below KKM in the subject of Islamic Cultural History at MTsN Padang Panjang. To help solve these problems, researchers are interested in trying the Value Clarification Technique learning model to improve student learning outcomes. The type of this research is experimental with Randomized Control Group Posttest Only Design. The population in this research is VIII class at MTsN Padang Panjang. The sample is selected purposively from a specific population. Researchers chose class VIII E as the experimental class, and class VIII C as the control class. The instrument used is a test. For testing research hypotheses, researchers use t-tests and data processing using SPSS. The results of this study concluded that the Value Clarification Technique learning model is effective for student learning outcomes in the subject of Islamic Cultural History. Based on data analysis that shows the tcount results are greater than ttable. Tcount is 84.094 and ttable is 1.670. The average score in the experimental class is 88,37 and the average score in class VIII C is 71,15.